PENGARUH SOCIAL MEDIA CONTENT INSTAGRAM @BYU.ID TERHADAP BRAND IMAGE PROVIDER DIGITAL BY.U (Survei Pada Followers Akun Instagram @byu.id) - Ayu Widya Lestari (2022)
Nowadays, the telecommunications industry in Indonesia has grown rapidly. Its development is as a result of the increasing number of Internet usage. This has made various service providers always provide the best products and always give them a greeting. telecommunications, their target market is also targeting Gen Z. The purpose of this study is to find out how much influence Instagram @byu.id's Social Media Content has on Brand Image. A total of 100 respondents became obj penri Instagram followers @byu.id. used is quantitative with the type of explanatory research, survey research methods and using Cognitive Response Theory as the basis for the assumptions of the media of this study. The results of the correlation test in this study. bro, the brand image is 0.580. The results of the coefficient test of determination stated that there was an influence caused by social media content of 34.2% on brand image. Linear regression results showed that for every 1% addition of social media content, before 38 hypothesis testing, it was found that t count > t table, which was 7.135. This research shows that there is a significant effect between social media content on Instagram @byu.id on the brand image of Digital Provider By.U.